2001
DOI: 10.1021/ja005685h
|View full text |Cite
|
Sign up to set email alerts
|

Imidotitanium Complexes as Hydroamination Catalysts:  Substantially Enhanced Reactivity from an Unexpected Cyclopentadienide/Amide Ligand Exchange

Abstract: The addition of an N-H bond across a carbon-carbon double or triple bond is potentially one of the most direct and efficient methods of alkylating an amine. Considerable effort has been expended in the search for transition metal complexes that will catalyze this desirable transformation, and while notable successes have been realized, general solutions to the problem have proven elusive. 1 As a consequence, the discovery and development of hydroamination reactions remain important goals.Relatively few early t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(206 citation statements)
references
References 21 publications
6
195
0
5
Order By: Relevance
“…In search of a more convenient synthesis of aldehyde 5, we then found that lithiated indene (12) smoothly undergoes a nucleophilic substitution reaction with commercially available and inexpensive 2-bromo-1,1-diethoxyethane (13) to give the corresponding indenylethylacetal 14 in excellent yield of 98 % (Scheme 5). After aqueous work-up, acetal 14 was already obtained with high purity (97 % as determined by GC analysis) and therefore, the crude product could directly be used for the subsequent acetal cleavage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In search of a more convenient synthesis of aldehyde 5, we then found that lithiated indene (12) smoothly undergoes a nucleophilic substitution reaction with commercially available and inexpensive 2-bromo-1,1-diethoxyethane (13) to give the corresponding indenylethylacetal 14 in excellent yield of 98 % (Scheme 5). After aqueous work-up, acetal 14 was already obtained with high purity (97 % as determined by GC analysis) and therefore, the crude product could directly be used for the subsequent acetal cleavage.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is well established that in the presence of amines, bis(η 5 -cyclopentadienyl)titanium precursors (Cp 2 TiL n ) undergo an unexpected cyclopentadienide/amide ligand exchange reaction that results in the formation of mono(η 5 -cyclopentadienyl)titanium(amido) complexes (Cp(RNH)TiL n , Scheme 2). 13 In analogy, it can be assumed that the catalyst precursor Ind 2 TiMe 2 used for hydroaminoalkylation reactions of alkenes undergoes a comparable ligand exchange reaction with the amine substrate and as a result, the expected catalytically active titanaaziridine formed from Ind 2 TiMe 2 possesses only one indenyl ligand and an amido ligand (Scheme 2). However, these two ligands are expected to remain bonded to the titanium center during the entire catalytic cycle and as a consequence, they both determine the activity of the catalytic species.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: allenes · density functional calculations · hydroamination · reaction mechanisms · zirconium ly proposed by Bergman and co-workers for intermolecular alkyne and allene hydroamination with primary amines mediated by zirconocene compounds [8] and was later extended to cyclohydroamination. [6] Various experimental studies, [9] of which the detailed kinetic investigation of Doye [9a] is most notable, and also computational [10] examination have substantiated this mechanism.…”
Section: A C H T U N G T R E N N U N G (Nhr)mentioning
confidence: 99%
“…This scenario is similar to the mechanism established for the Zr-catalysed intermolecular hydroamination of alkynes and allenes with primary amines. [8] The kinetically most demanding step of the productive cycle (i.e., 9 A!12 A along the predominantly traversed branch) has a somewhat lower barrier (DG°= 28.8 kcal mol À1 , Scheme 10).…”
mentioning
confidence: 99%
“…There has been much interest in using them as starting material for the synthesis of allylamines. Only a small number of transition-metal catalyzed intermolecular hydroamination reactions of allenes have been described [9][10][11][12][13][14]. Previously, we reported the addition of amines to allene using Pd(OAc) 2 , from which a mixture of the desired allylic amine and a minor amount of dienic amine was obtained [15].…”
Section: Introductionmentioning
confidence: 99%